Clinical and cognitive trajectories in cognitively healthy elderly individuals with suspected non-Alzheimer's disease pathophysiology (SNAP) or Alzheimer's disease pathology: a longitudinal study. Issue 10 (September 2016) - Burnham, Samantha C; Bourgeat, Pierrick; Doré, Vincent; Savage, Greg; Brown, Belinda; Laws, Simon; Maruff, Paul; Salvado, Olivier; Ames, David; Martins, Ralph N; Masters, Colin L; Rowe, Christopher C; et al.
Summary: Background: Brain amyloid β (Aβ) deposition and neurodegeneration have been documented in about 50–60% of cognitively healthy elderly individuals (aged 60 years or older). The long-term cognitive consequences of the presence of Alzheimer's disease pathology and neurodegeneration, and whether they have an independent or synergistic effect on cognition, are unclear. We aimed to characterise the long-term clinical and cognitive trajectories of healthy elderly individuals using a two-marker (Alzheimer's disease pathology and neurodegeneration) imaging construct. Methods: Between Nov 3, 2006, and Nov 25, 2014, 573 cognitively healthy individuals in Melbourne and Perth, Australia, (mean age 73·1 years [SD 6·2]; 58% women) were enrolled in the Australian Imaging, Biomarker and Lifestyle (AIBL) study. Alzheimer's disease pathology (A) was determined by measuring Aβ deposition by PET, and neurodegeneration (N) was established by measuring hippocampal volume using MRI. Individuals were categorised as A − N −, A + N −, A + N +, or suspected non-Alzheimer's disease pathophysiology (A − N +, SNAP). Clinical progression, hippocampal volume, standard neuropsychological tests, and domain-specific and global cognitive composite scores were assessed over 6 years of follow-up. Linear mixed effect models and a Cox proportional hazards model of survival were used to evaluate, compare, and contrast the clinical, cognitive, and volumetric trajectories of patients in the four AN categories. Findings: 50 (9%) healthy individuals were classified as A + N +, 87 (15%) as A + N −, 310 (54%) as A − N −, and 126 (22%) as SNAP. APOE ε4 was more frequent in participants in the A + N + (27; 54%) and A + N − (42; 48%) groups than in the A − N − (66; 21%) and SNAP groups (23; 18%). The A + N − and A + N + groups had significantly faster cognitive decline than the A − N − group (0·08 SD per year for AIBL-Preclinical AD Cognitive Composite [PACC]; p<0·0001; and 0·25; p<0·0001; respectively). The A + N + group also had faster hippocampal atrophy than the A − N − group (0·04 cm 3 per year; p=0·02). The SNAP group generally did not show significant decline over time compared with the A − N − group (0·03 SD per year [p=0·19] for AIBL-PACC and a 0·02 cm 3 per year increase [p=0·16] for hippocampal volume), although SNAP was sometimes associated with lower baseline cognitive scores (0·20 SD less than A − N − for AIBL-PACC). Within the follow-up, 24% (n=12) of individuals in the A + N + group and 16% (n=14) in the A + N − group progressed to amnestic mild cognitive impairment or Alzheimer's disease, compared with 9% (n=11) in the SNAP group. Interpretation: Brain amyloidosis, a surrogate marker of Alzheimer's disease pathology, is a risk factor for cognitive decline and for progression from preclinical stages to symptomatic stages of the disease, with neurodegeneration acting as a compounding factor. However, neurodegeneration alone does not confer a significantly different risk of cognitive decline from that in the group with neither brain amyloidosis or neurodegeneration. Funding: CSIRO Flagship Collaboration Fund and the Science and Industry Endowment Fund (SIEF), National Health and Medical Research Council, the Dementia Collaborative Research Centres programme, McCusker Alzheimer's Research Foundation, and Operational Infrastructure Support from the Government of Victoria.